ADLERIAN COUNSELING IN IDENTIFYING SELF-ESTEEM MANAGEMENT - Habsy, Bakhrudin All; Susanto, Adianna Muthia; Oetari, Aiuningtyas Yuni; Nishafa, Difani Khoirun (Jurnal Kajian Pendidikan dan Psikologi, 2025)
This study aims to describe in depth the role of Adlerian counseling in identifying the handling of self-esteem in individuals who experience feelings of inferiority. Self-esteem is an important aspect of psychological development that affects individual confidence, social relationships, and motivation in facing life's challenges. Adlerian counseling was chosen because it focuses on understanding feelings of inferiority, finding a purpose in life, and strengthening social interests that are relevant to the dynamics of self-esteem. The research method used is a qualitative approach with a case study design. The study participants consisted of four people who experienced low self-esteem problems with different backgrounds. Data were collected through in-depth interviews, observations during counseling sessions, and analysis of counseling reflection documents. The data was analyzed using thematic analysis techniques by maintaining validity through triangulation of sources and techniques. The results of the study showed that Adlerian counseling was able to identify factors that affect low self-esteem, both from negative beliefs and social pressure. Lifestyle analysis techniques, socratic dialogue, and encouragement are effective in helping participants change their perception of themselves and increase their courage to interact socially. The changes observed included increased confidence, courage to take on new responsibilities, and a reduction in withdrawal behavior. These findings confirm that Adlerian counseling is relevant to use as a self-esteem management strategy because it can integrate cognitive, emotional, and social aspects holistically.